Neuromuscular changes after a long distance triathlon World Championship - Cuba-Dorado, A.; Álvarez-Yates, T.; Carballo-López, J.; Iglesias-Caamaño, M.; Fernández-Redondo, D.; García-García, O. (European Journal of Sport Science, 2022)
This study aimed to determine the neuromuscular changes in muscle contractile properties and countermovement jump (CMJ) performance after a long distance (LD) triathlon, inquiring to what extent it is influenced by gender and the evaluated muscle, and to explore for response differences. Four elite (2 females and 2 males) and 18 well-trained triathletes (3 females and 15 males) who competed in the 2019 LD Triathlon World Championship undergone, prior and post-race, a CMJ and a muscle contractile properties assessment in vastus lateralis (VL) and biceps femoris (BF) using tensiomyography. A mixed ANOVA was carried out to detect triathletes` neuromuscular changes after the competition. A large decrease in jump height and flight time was found in CMJ (p = 0.001, Etap2 = 0.767) with gender differences (Etap2 = 0.308). contraction (Tc), delay (Td) and sustain times (Ts) also showed a large decrease (p = 0.001, Etap2 = 0.174-0.413). However, maximum radial muscle belly displacement was not altered by the competition, but did greatly increase radial displacement velocity (p = 0.031; Etap2 = 0.212). No gender differences were found in contractile properties. Correlation analysis between race performance and the jumping and tensiomyography parameters only showed a moderate negative correlation with Tc of the BF in pre- and post-competition (r = -0.44; -0.43; p = 0.05). In conclusion, triathletes after a LD World Championship suffer a sharp drop in jump performance and variations in VL`s and BF`s contractile properties, showing decreases in Tc, Td and Ts without gender differences. The regular use of these parameters can allow the monitoring of triathlete's neuromuscular fatigue and aid in the distribution of more efficient loads in their training cycles.